2014
DOI: 10.1152/ajpheart.00696.2013
|View full text |Cite
|
Sign up to set email alerts
|

NADH changes during hypoxia, ischemia, and increased work differ between isolated heart preparations

Abstract: Wengrowski AM, Kuzmiak-Glancy S, Jaimes R 3rd, Kay MW. NADH changes during hypoxia, ischemia, and increased work differ between isolated heart preparations. Am J Physiol Heart Circ Physiol 306: H529 -H537, 2014. First published December 13, 2013; doi:10.1152/ajpheart.00696.2013.-Langendorff-perfused hearts and working hearts are established isolated heart preparation techniques that are advantageous for studying cardiac physiology and function, especially when fluorescence imaging is a key component. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 28 publications
6
56
0
Order By: Relevance
“…In contrast, another uncoupler blebbistatin in three experiments postponed the adverse electrophysiological outcomes of ischemia (not shown) consistent with results from our recent study (56). Lack of mechanical load in the Langendorff-perfused hearts could also distort the ischemic changes (62) …”
Section: Resultssupporting
confidence: 89%
“…In contrast, another uncoupler blebbistatin in three experiments postponed the adverse electrophysiological outcomes of ischemia (not shown) consistent with results from our recent study (56). Lack of mechanical load in the Langendorff-perfused hearts could also distort the ischemic changes (62) …”
Section: Resultssupporting
confidence: 89%
“…Blebbistatin was previously shown to affect electrophysiology (4) but not to interfere with the mechanism of VF (13) in normoxemic hearts. However, Wengrowski et al (32) have recently demonstrated that blebbistatin dramatically postpones NADH accumulation during acute ischemia, indicating a significant interference of this drug in the natural course of ischemic events (32). Clearly, our study extends their observation, demonstrating that blebbistatin also postpones ⌬⌿ m collapse and asystole.…”
Section: Discussionsupporting
confidence: 73%
“…Blebbistatin, a recently discovered selective inhibitor of myosin II ATPase, has become a "standard of care" electromechanical uncoupler for use in experimental studies involving optical mapping or confocal imaging, including those addressing effects of I/R on electrophysiological parameters and ⌬⌿ m dynamics (6, 23, 24). It was recently shown that blebbistatin postpones changes in cellular redox state associated with ischemia (32). So it was important to test whether blebbistatin also modulates the time of ischemic electrical failure and ⌬⌿ m loss.…”
Section: Figuresmentioning
confidence: 99%
“…Blebbistatin is a popular uncoupling agent for optical mapping, especially when imaging Ca i 2ϩ because it specifically inhibits the myosin ATPase without altering sarcolemmal ion currents or SR Ca 2ϩ kinetics (28). However, myocyte ATP utilization is severely reduced by electromechanical uncoupling, potentially altering the time course of physiological changes, especially mitochondrial function, during experimental perturbations (47,105,114). Motion tracking algorithms (41,80,115) and ratiometry (42,44,93) are sometimes effective in removing motion artifact from optical action potentials, but there has been less work in the application of motion tracking algorithms to reduce artifact in optically mapped Ca i 2ϩ transients.…”
Section: Optical Mapping Ca I 2ϩ Fluorescence From Myocardial Tissuementioning
confidence: 99%